Postoperative unexplained sigmoid stenosis in a patient with rectal cancer complicated with connective tissue disease: a case report and literature review - Tong, Deming; Li, Jian; Gao, Guangrong; Zhang, Cheng (Frontiers in Oncology, 2024)
It is well established that host immunity plays a critical role in defending against colorectal cancer (CRC) progression. Connective tissue disease (CTD) encompasses a group of heterogeneous, immune-mediated disorders that present with diverse and often non-specific initial symptoms. Raynaud’s phenomenon is a common feature, complicating early diagnosis. As CTD progresses, it can damage the skin, muscles, and blood vessels and may extend to the lungs, heart, kidneys, and other abdominal organs. Several studies have reported that CTD can lead to intestinal vascular occlusion and related inflammation, but the occurrence of related complications after intestinal surgery has been reported rarely. In this study, an elderly female patient with rectal cancer complicated with CTD was found to have unexplained proximal anastomotic stenosis during an attempt at fistula restoration 3 months after laparoscopy-assisted transanal total mesorectal excision (TaTME) and preventive terminal ileostomy, resulting in fistula failure. This case study aims to serve as a reference for clinicians in their future practice.